The Information Technology Enabled Entrepreneurial Culture as an Antecedent of Firm’s Performance of Rubber and Plastic Manufacturing Firms in Thailand: The Moderating Role of Supply Chain Technology Adoption - Natnaporn Aeknarajindawat; Jetsalid Anesukanjanakul; Pornkul Suksod; Kulnaree Maneechote (International Journal of Supply Chain Management, 2019)
This research examines the association between entrepreneurship, two types of IT (the managerial IT resources and Technology IT resources), and performance of firm. The research supports the capabilities enabled through IT for organizations. Cross-sectional survey data has been used for testing the hypotheses and proposed research model from a sample of 203 leading firms in Thailand. The results of data analysis show that the culture of entrepreneurship is an important capability, which can forecast the market performance of a firm. A positive influenced is created on the establishment of entrepreneurship culture in an organization by the managerial and technological IT resources. The performance of a firm is positively influenced by the managerial and technological IT resources through the entrepreneurship culture capability. The findings of this research have important implications for the managers. It has been suggested by the results that use of managerial and technological IT resources increases the ability of firm to establish a culture that supports innovation. Another important implication is related to the intermediation capability of organization that is entrepreneurship culture. It converts both managerial and technological IT resources into the performance outcomes. The research reveals the way in which entrepreneurship culture can be developed by firms. The crucial role of IT based resources is revealed in the development of organizational culture. Moreover, the paper reflects empirically and theoretically, the way in which business value can be generated by firms from the entrepreneurship culture supported by IT. This topic has received very limited attention.